The Use of Machine Translation Tools on EFL Students’ Writing - Tanjung, Firima Zona; Kusmaryani, Woro (Linguistics and ELT Journal, 2025)
Despite the increasing prominence of machine translation (MT) tools in academic settings, few studies have explored how EFL students balance the use of translation techniques with digital assistance while also enhancing their writing skills. This research investigates how fourth-semester EFL students translate and articulate their views on utilizing MT tools to support academic writing. The fourth semester students enrolling translation course in an undergraduate program in a public university in Indonesia participated in this mixed method research. Data were gathered from documents, questionnaire, and interview which then analyzed with qualitative method and descriptive statistical analysis. The findings reveal that borrowing and literal translation were the most frequently used techniques, followed by transposition and adaptation. It indicates students’ reliance on direct linguistic transfer and their emerging grammatical flexibility and cultural awareness. Although the students acknowledged the limitations of MT tools and the need for critical post-editing, they had positive attitudes toward MT tools usage. The study concludes that students are in a transitional phase of translation competence. Hence, pedagogical interventions—emphasizing writing conventions, post-editing skills, and MT literacy including etiquette—are highly required for endorsing the development of both translation and academic writing skills in EFL academic settings.